Optimasi Media Pendingin untuk Meningkatkan Kekerasan Permukaan Baja Karbon Rendah melalui Proses Carburizing - Atmoko, Nugroho; Alfarizie, Tito; Pisti Cikarge, Ghia; Wijayanto, Hendi; Suseno, Ibnu (Sekolah Tinggi Teknologi Kedirgantaraan, 2025)
Carburizing is one of the most effective heat treatment methods to enhance the surface hardness of low-carbon steel by diffusing carbon atoms into the material's surface layer. The final characteristics of the carburized layer are strongly influenced by the quenching medium applied after the heating process. This study aims to analyze the effect of various quenching media on the microstructure and hardness of low-carbon steel specimens subjected to pack carburizing. The quenching media used include air, distilled water, and oil. Vickers hardness testing was conducted across the cross-section of the specimens, and microstructural characterization was performed using optical microscopy. The results show that air cooling produced a ferrite–pearlite structure with a diffusion layer thickness of approximately 188 µm and a hardness of 384 HV. Quenching with distilled water and oil resulted in a mixed structure of fine pearlite and partial martensite with hardness ranging from 780 to 820 HV. These findings indicate that oil is a promising alternative quenching medium for enhancing surface hardness without reducing the toughness of the core material.